2011
DOI: 10.3390/ijms12107199
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxidative Stress, Apoptosis, PGC-1α and Mitochondrial Biogenesis in Cerebral Ischemia

Abstract: The primary physiological function of mitochondria is to generate adenosine triphosphate through oxidative phosphorylation via the electron transport chain. Overproduction of reactive oxygen species (ROS) as byproducts generated from mitochondria have been implicated in acute brain injuries such as stroke from cerebral ischemia. It was well-documented that mitochondria-dependent apoptotic pathway involves pro- and anti-apoptotic protein binding, release of cytochrome c, leading ultimately to neuronal death. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(243 citation statements)
references
References 102 publications
4
227
1
11
Order By: Relevance
“…The action of PGC-1a is also related to control of oxidative stress. 26 Overproduction of ROS, a by-product of mitochondrial electron transport chain, has been implicated in acute brain injuries such as ischemia. 26 Our results showed that fructose exacerbated the effects of TBI on the levels of 4HNE, as indicative of increased lipid peroxidation and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The action of PGC-1a is also related to control of oxidative stress. 26 Overproduction of ROS, a by-product of mitochondrial electron transport chain, has been implicated in acute brain injuries such as ischemia. 26 Our results showed that fructose exacerbated the effects of TBI on the levels of 4HNE, as indicative of increased lipid peroxidation and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…26 Overproduction of ROS, a by-product of mitochondrial electron transport chain, has been implicated in acute brain injuries such as ischemia. 26 Our results showed that fructose exacerbated the effects of TBI on the levels of 4HNE, as indicative of increased lipid peroxidation and neuronal damage. It could be argued that the high oxygen supply necessitated for the delivery of anesthesia could influence the outcome of the brain injury by altering cerebral metabolism and ROS levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPactivated protein kinase, which guards against deficient ATP regeneration by upregulating catabolic pathways including glycolysis, 30 likely contributes to the upregulation of MCTs in response to hypoxia and increased activity-dependent energy demand in the brain, such as observed for MCT1 and MCT4 in heart and skeletal muscle on chronic stimulation or exercise. 31 The transcriptional coactivator PGC-1α (peroxisome proliferatoractivated receptor-γ (PPARγ) coactivator-1α), a master regulator of reactive oxygen species scavenging enzymes and of mitochondrial biogenesis in brain, 32 may also participate. Thus, PGC-1α 33 is known to upregulate MCTs in other tissues, and so does PPARα, 34 which mediates adaptive responses to energy restriction and induces the formation of ketone bodies.…”
Section: Monocarboxylate Transportersmentioning
confidence: 99%
“…To restrict our analyses to putative HuR targets, we examined whether the human homologs of these 61 mRNAs were identified to physically interact with HuR in PAR-CLiP 36,37 assays deposited in the DoRiNA 38 database; based on phenotypic relevance, we selected six such mRNAs. These included mRNAs encoding for: (a) major energy sensors involved in oxidative metabolism such as Ppargc1a (aka PGC1α), which is a master regulator of ROS-scavenging enzymes, and mitochondrial biogenesis, previously shown to counteract cerebral ischemia; 39 and NQO1 (NAD(P)H dehydrogenase, quinone 1), a major antioxidant whose dysfunction associates with many disease states and cancer; 40 (b) pleiotropic controllers involved in cell survival and cell stress such as Myc 41 and Cirbp (cold-inducible RNA-binding protein); 42 and (c) factors involved in neuronal polarity and plasticity such as semaphorin 3a (Sema3a) and Gja1 (connexin-43). 43 One gene that associated with Elavls but was not identified in DoRiNA (Prkar2a) was also selected because of the relevance of protein kinase A signals to neuronal excitation.…”
Section: Hur Targets and Regulates A Group Of Rnas Involved In Oxidatmentioning
confidence: 99%